Impact of age on PUAL as an indicator of opioid effect in adult subjects - McKay, Rachel Eshima; Kohn, Michael A.; Larson, Merlín D. (Journal of clinical monitoring and computing, 2025)
Opioid-induced respiratory depression (OIRD) remains a critical safety concern, particularly in older adults, yet timely, reliable detection methods are limited. Decline of pupillary unrest in ambient light (PUAL) has demonstrated potential as a marker of opioid effect in young adult subjects. We evaluated whether previously observed PUAL thresholds for high-risk opioid exposure in younger adults remain valid in 40-60-year-old subjects. Ten healthy volunteers 40–60 years of age underwent PUAL measurement at baseline and every 2.5 min during a 10-minute remifentanil infusion (0.2–0.3 µg/kg/min) and 25-minute recovery period. High-risk opioid exposure was defined primarily by modeled remifentanil effect-site concentration (CEREMI) threshold during infusion. Findings were then combined with previously collected data from 20 younger subjects (aged 20–39 years) undergoing an identical infusion protocol. PUAL declined consistently during infusion and increased toward baseline during recovery ( p < 0.001). During infusion no significant difference in slope over time or CEREMI was observed between age groups, but during recovery a flatter slope was observed in older subjects ( p = 0.016). PUAL reliably distinguished between high-versus low-risk opioid exposure during infusion (AUROC = 0.9833 [95% CI: 0.8935, 0.9995]), with interval likelihood ratio (iLR) for high-toxic opioid effect 27.98 (95% CI: 1.79, 438.33) for PUAL < 0.04, 0.75 (95% CI: 0.38, 1.50) for PUAL 0.04-< 0.14, and 0.030 (95% CI: 0.002, 0.477) for PUAL ≥ 0.14. Comparison of discriminatory performance to that of younger subjects showed no significant difference (chi2 = 1.02, p = 0.3129). PUAL thresholds for high-risk opioid exposure are consistent between younger and older adults and do not require age-specific adjustment up to age 60. PUAL offers a reliable, real-time marker of opioid effect with potential to enhance early OIRD detection in adults.